Aural Myiasis, a Rare Cause of Earache - Ibrahim Al Jabr (Case Reports in Otolaryngology)
Myiasis of the ear is an infestation of the ear by maggots (the larval stage of flies). In the literature, there are only few cases reported about aural myiasis. It is more common to occur in tropical regions, where humidity and warm weather provide a good environment for this infestation. In this paper, a 12-year-old boy is reported to have unilateral earache for 3-day duration. Examination of the painful ear showed a tympanic membrane perforation with larvae (maggots) in the middle ear. They were removed by using a forceps and gentle irrigation of ear to expel any remnant. Further management included assessment of hearing, computed tomography (CT) scan, and outpatient follow-up.